Analisis Kebutuhan Gizi Dan Perencanaan Menu Gizi Seimbang Dalam Layanan Makanan Institusi Pendidikan Tinggi - Marifat Istiqa Mukty; Andi Dhini Alfiani (Jurnal Sains dan Kesehatan, 2022)
food service in higher education institutions has an important role in supporting the health and well-being of students and staff. However, often the lack of attention to nutritional needs and the variety of menus can lead to health problems and lack of user satisfaction. In the context of increasing awareness of the importance of nutrition in supporting health and academic performance, this study fills a knowledge gap on how food services in higher education institutions can meet nutritional needs by presenting a nutritionally balanced menu. Therefore, this study aims to investigate the nutritional needs and plan a balanced nutrition menu in food services in higher education institutions. This study used observational study design. The Data was collected through a survey of 300 students and 100 staff from several higher education institutions in a particular city. The survey included questions about eating habits, food preferences, nutritional knowledge, and satisfaction with existing menus. In addition, direct observation was also made of the menu served in the campus cafeteria. Analysis of the data showed that the majority of respondents had limited nutritional knowledge and tended to consume fast food. The variety of menus offered is also limited, with deficiencies in serving nutritionally balanced meals. However, the majority of respondents expressed a desire to have more access to a nutritionally balanced menu. The results of this study highlight the importance of raising awareness of nutrition and offering a balanced variety of menus in higher education institutions. The discussion also includes the practical implications of these findings in improving the health and academic performance of the campus community. This study confirms the importance of nutritional needs analysis and balanced nutrition menu planning in food services in higher education institutions. Providing a balanced menu can improve the health and well-being of students and staff.